Natural Compound Shikonin Is a Novel PAK1 Inhibitor and Enhances Efficacy of Chemotherapy against Pancreatic Cancer Cells - Wenjing Ji; Xiaoyan Sun; Yang Gao; Man Lu; Lingxia Zhu; Dawei Wang; Chunping Hu; Jiao Chen; Peng Cao (Molecules, 2022)
Shikonin is the main component of root extracts from the Chinese herbal medicine Lithospermum erythrorhizon, which is commonly used for the treatment of various diseases including cancer. Previous research showed that shikonin suppressed pancreatic cancer growth; nevertheless, its molecular targets and mechanisms have not been elucidated. This study aimed to investigate the interaction and regulatory mechanisms of shikonin on its potential target p21-activated kinase 1 (PAK1). Through a labchip-based screening method, shikonin was identified as a potential bioactive PAK1 inhibitor. Molecular docking technology was used to detect the interaction sites of shikonin and PAK1 kinase. Western blot was performed to validate the mechanism. MTT and flow cytometry were practiced to investigate the effect of shikonin against pancreatic cancer cells. The results show that shikonin significantly inhibited the activity of PAK1 kinase with IC50 value of 7.252 ± 0.054 μM. Molecular docking studies showed that shikonin binds to the ATP-binding pocket of the PAK1 kinase domain. Moreover, shikonin inhibited PAK1 activation and its downstream signaling pathway proteins, while reducing proliferation and inducing apoptosis of pancreatic cancer cells. Further studies showed that the treatment of shikonin sensitized pancreatic cancer cells to chemotherapeutic drugs. These results suggest that shikonin, a potential natural inhibitor targeting PAK1 kinase, has promising potent applications in the treatment of pancreatic cancer and chemotherapy sensitization.